THE FIRST FIND OF RHYNCHOLITES FROM THE MIDDLE JURASSIC OF THE CRIMEAN MOUNTAINS - Komarov V.N. (My University, 2002)
A new rhyncholite species, Akidocheilus (Akidocheilus) costatisulcatus, is described from the Biyuk-Yanyshar Ridge. This is the first record of rhyncholites from the Lower Callovian of the Crimean Mountains.
Keywords: Jurassic; Mesozoic::Jurassic; Мезозой::Юрская